MiRNA sequencing of platelet and exosome revealed platelet miR-199b-3p as a potential biomarker in lung adenocarcinoma - Wen, Xiaoxia; Yu, Sisi; Leng, Ping; Liu, Yu; Luo, Huaichao (Frontiers in Immunology, 2025)
BackgroundDistinguishing malignant lung adenocarcinoma (LAC) from benign pulmonary nodules (BPN) is a major clinical challenge. While exosomal microRNAs (miRNAs) are established liquid biopsy biomarkers, tumor-educated platelet miRNAs represent an emerging source. However, a direct comparison of the diagnostic potential between these two sources, and the identification of reliable platelet miRNA biomarkers for LAC, remain poorly defined. Critically, the well-documented interaction between tumor-derived exosomes and platelets, which complicates exosome isolation due to inevitable platelet contamination, raises a pivotal question: Could the analysis of platelet miRNA, a far easier-to-isolate component, offer a viable and efficient alternative to exosome-based diagnostics?MethodsWe performed miRNA sequencing (miRNA-seq) on paired peripheral blood platelets and plasma exosomes from healthy donors (HD), BPN, and LAC patients. The abundance and diversity of miRNAs were compared. Candidate reference miRNAs for platelet studies were screened and validated using RT-qPCR and multiple stability algorithms. Differentially expressed platelet miRNAs were identified and validated in a cohort of 133 subjects (70 LAC, 31 HD, 32 BPN). The diagnostic performance of the top candidate was evaluated using ROC analysis and Net Reclassification Index (NRI) against traditional biomarkers (CEA) and clinical models. Target genes were predicted using bioinformatic tools and validated with public databases (TCGA, UALCAN, GEPIA).ResultsPlatelets contained significantly greater miRNA diversity and abundance compared to exosomes. Differentially expressed platelet miRNAs showed higher concordance with tissue-specific signatures than their exosomal counterparts. hsa-let-7i-5p was identified as the most stable reference miRNA for normalizing platelet miRNA expression in LAC. hsa-miR-199b-3p was significantly downregulated in the platelets of LAC patients compared to both HD and, crucially, BPN patients. It effectively distinguished LAC from BPN (AUC = 0.73) and early-stage LAC (Stage I) from BPN (AUC = 0.72), outperforming traditional biomarkers (CEA) and clinical models, as confirmed by significant NRI values. The diagnostic value of miR-199b-3p was also significant in the non-GGN subgroup (p=0.037). Bioinformatic analysis predicted KTN1 as a key target gene, with an inverse correlation to miR-199b-3p in LAC tissues and association with poor prognosis. Intriguingly, KTN1 expression in platelets was also dysregulated, suggesting a complex platelet-tumor interaction.ConclusionThis study demonstrates that platelet miRNAs are a superior source for liquid biopsy in LAC compared to exosomal miRNAs. We establish hsa-let-7i-5p as a reliable reference gene and identify platelet hsa-miR-199b-3p as a promising non-invasive biomarker for the differential diagnosis of malignant and benign pulmonary nodules, offering a new avenue for the early detection of lung adenocarcinoma.